Beta-adrenergic receptor blockade in angiosarcoma: Which beta-blocker to choose? - Embaby, Alaa; van Merendonk, Lisanne; Steeghs, Neeltje; Beijnen, Jos; Huitema, Alwin (Frontiers in Oncology, 2022)
Beta-blockers are currently studied to improve therapeutic options for patients with angiosarcoma. However, most of these patients have no cardiovascular co-morbidity and it is therefore crucial to discuss the most optimal pharmacological properties of beta-blockers for this population. To maximize the possible effectiveness in angiosarcoma, the use of a non-selective beta-blocker is preferred based on in vitro data. To minimize the risk of cardiovascular adverse events a beta-blocker should ideally have intrinsic sympathomimetic activity or vasodilator effects, e.g. labetalol, pindolol or carvedilol. However, except for one case of carvedilol, only efficacy data of propranolol is available. In potential follow-up studies labetalol, pindolol or carvedilol can be considered to reduce the risk of cardiovascular adverse events.